TRANSFORMASI PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEWUJUDKAN TRAUMA-SENSITIVE ISLAMIC EDUCATION - Nabilah, Maryam (As-Sulthan Journal of Education, 2026)
This study aims to map the construction of the role of Islamic Religious Education (PAI) teachers from the perspective of Trauma-Sensitive Islamic Education (TSIE) in response to the growing need for safe, empathetic pedagogical practices that support students' psycho-spiritual recovery. Using a qualitative approach based on a literature review, this study examines literature related to Islamic pedagogy, trauma psychology, spiritual care, and the concept of trauma-informed education to develop a comprehensive theoretical framework. The analysis was conducted using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that TSIE reconstructs the role of Islamic Religious Education teachers into four main domains: (1) Trauma-Sensitive Pedagogical Praxis, namely the restructuring of teaching practices that are gentle, predictable, and avoid triggers of trauma; (2) Emotional Counseling, which is providing emotional and spiritual support through empathy, validation, and a calming relational presence; (3) Spiritual Calming Agency, namely the use of prayer, dhikr, and tadabbur as strategies for emotional regulation and inner recovery; and (4) Safe Space Learning Ecology, namely the development of a safe, supportive, and threat-free classroom ecosystem as a foundation for effective learning. This research confirms that TSIE provides a conceptual foundation for Islamic education that is more humanistic, holistic, and responsive to the psychosocial dynamics of students. However, its implementation requires strengthening teacher capacity through trauma sensitivity training and consistent integration of pedagogical-spiritual practices. Further research is needed to empirically test this model through case studies or classroom ethnography.